Hypotensive effect and toxicology of the extract from Coscinium fenestratum (Gaertn.) Colebr. - T. Wongcome (2018)
The water extract from Coscinium fenestratum (Gaertn.) Colebr. (CF extract) was tested for hypotensive and vasorelaxant effects. Acute and subchronic toxicity as well as motor activity of CF extract were also evaluated. The present study demonstrates that CF extract is effective in reducing blood pressure in anesthetized normotensive rats. This effect is shown to be dose-related and rapid in onset. The extract showed an endothelium-dependent and independent vasorelaxant activity in isolated aortic rings precontracted with phenylephrine (1 μM) and KCl (60 mM). The capacity of l-NAME (100 μM), an inhibitor of nitric oxide synthase, to reduce the vasorelaxant action of the extract indicates the involvement of nitric oxide. In the acute toxicity test, an oral dose of 5000 mg/kg of the CF extract did not produce mortality or significant changes of the general behavior of animals and gross appearance of internal organs of rats. Similarly, in the subchronic toxicity test, an oral dose of 2500 mg/kg/day of the CF extract given to rats for 90 days did not cause any significant change of any of the parameters observed when compared with those of the control animals. Moreover, the CF extract did not produce any effect on the central nervous system when spontaneous motor activity in rats was assessed. However, because some average hematological and blood chemistry values were found to be statistically different, further studies, including chronic toxicity test, should be done to confirm the safety of this plant when it is used over a long period of time. © 2007 Elsevier Ireland Ltd. All rights reserved.